ANALISIS USAHA TAMBAK UDANG PUTIH (Litopenaeus vannamei) DI CV SUNGAI RINDAM DESA LALANG KECAMATAN MEDANG DERAS KABUPATEN BATUBARA - Veni Selvianty Zebua; Pindi Patana; Febrina Arli (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
White prawn represent fishery com modity which in this time is liking by manypeople. This matter because of white prawn more free and hold up to disease and alsorepresent prospect of effort promising to cultivator. Effort prawn conducting at whiteprawn fishpond CV. Sungai Rindam in Countryside Lalang Sub-District of MedangDeras of District Batubara is the effort magnification with white prawn commodity.This research aim to know pattern exploiting of activity conducting and elegibilityfinancial of activity fishpond. This matter is done to study effort of conducting ifcompetent or not to be developed. Pursuant to analysis of effort which is can know thateffort White Prawn fishpond of Coast Perjuangan in District of Medang Deras is profit.Result of analysis elegibility of finansial is effort and sensitivity got value of NPVpositive, Net B/C> 1 and IRR > rate discount. Calculation of sensitivity analasysconducted to fry increase of price equal to 6,06% and degradation of price sell prawnequal to 2,89%, showing this effort still competent to be run. Result of which isobtained from this research indicate that the effort white prawn fishpond CV. SungaiRindam Sub-District of Medang Deras is competent to be run and developed.Keywords: White Prawn farming in Batubara, Analysis Elegibility of Effort.